The use of waste materials for concrete production in construction applications - Ashraf, Teara; Doh, Shu Ing; Vivian W. Y., Tam (IOP Publishing Ltd, 2018)
To sustain the environment, it is crucial to find solutions to deal with waste, pollution, depletion and degradation resources. In construction, large amounts of concrete from buildings’ demolitions made up 30-40 % of total wastes. Expensive dumping cost, landfill taxes and limited disposal sites give chance to develop recycled concrete. Recycled aggregates were used for reconstructing damaged infrastructures and roads after World War II. However, recycled concrete consists fly ash, slag and recycled aggregate, is not widely used because of its poor quality compared with ordinary concrete. This research investigates the possibility of using recycled concrete in construction applications as normal concrete. Methods include varying proportion of replacing natural aggregate by recycled aggregate, and the substitute of cement by associated slag cement with fly ash. The study reveals that slag and fly ash are effective supplementary elements in improving the properties of the concrete with cement. But, without cement, these two elements do not play an important role in improving the properties. Also, slag is more useful than fly ash if its amount does not go higher than 50%. Moreover, recycled aggregate contributes positively to the concrete mixture, in terms of compression strength. Finally, concrete strength increases when the amount of the RA augments, related to either the high quality of RA or the method of mixing, or both.